The Influence of changes in Personal Income Tax Rate towards tax compliance by inttention to comply and tax knowledge as mediating variable - Pramita Sukma Wardani (INVENTORY: JURNAL AKUNTANSI, 2023)
The Objective of this research study is to examine the effect of attitude toward tax compliance on compliance pay tax through the inttention to comply and to examine the effect of sosialization on compliance pay tax through tax knowledge. Data collected from questionnaire and analyzed with PLS-based SEM techniques with software SmartPLS version 4.0. The result of the analysis show both attitude toward tax compliance were found to be significantly on compliance pay tax through the inttention to comply and the effect of sosialization also have a significant effect on compliance pay tax through tax knowledge